AUDIT PENGELOLAAN KEUANGAN RUMAH TANGGA TERHADAP GAYA HIDUP IBU-IBU DI KP. CISASAH DESA PURWASARI, KEC. DRAMAGA, KAB. BOGOR - Nanda; Jumanti, Nani (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
The imbalance between household income and expenditure is becoming an increasingly common issue in society, especially among housewives. A consumptive lifestyle, lack of financial planning, and low awareness of budget management are often the main causes of financial problems that affect family stability. Based on this, this study was conducted to understand the relationship between household financial management audits and the lifestyles of mothers in villages, so as to provide an overview of the extent to which the implementation of household financial audits plays a role in creating family financial balance. A quantitative research method was used in this study. The population studied included all mothers who participated in this activity. The sampling technique used was saturated sampling, where the entire population was used as a sample of 46 people. Data collection was carried out using a questionnaire and a 5-point Likert scale. Data processing statistics used JAMOVI version 2.3.28. The results of the study indicate that Household Financial Management Audits have an impact on the lifestyles of mothers in Cisasah Village, Purwasari Village, Dramaga Subdistrict, Bogor Regency. Indicators in the Financial Management Audit variable include basic knowledge of financial management, credit management, savings and investment management, and risk management, which influence the lifestyles of mothers based on indicators of activity, interest, and opinion.